UNDERSTANDING THE DYNAMICS IN DEVELOPMENT PHILOSOPHY FOUNDATION GEOGRAPHY - Ida Bagus Made Astawa (Universitas Pendidikan Ganesha, 2016)
The development of the geography of the early to enter the melinium century has shifted significantly. In terms of approach, the geography has shifted from empirical science-analitycal to historical hermeneutic and critical. However, the shift from one approach to another an approach is not exclusive but rather the development of